Genetic Diversity and Drug Resistance Mutations in HIV-1 pol Gene Sequences in the Philippines: A Retrospective Genomic Analysis - Jennifer Ashley H. Reyes; Jarel Elgin Tolentino; RJ Tex C. Castillo; Peter Francis K. Dolores; Alfredo A. Hinay Jr (Journal of Pure and Applied Microbiology, 2024)
The Philippines has experienced a significant increase in HIV-1 infections in recent years, with a growing epidemic driven by the CRF01_AE strain. Understanding the genetic diversity of HIV-1 in the Philippines is crucial for the development of effective treatment strategies and the prevention of drug resistance. This study analyzed comprehensive data on common resistance mutation patterns from 2009 to 2017, revealing an increasing trend of mutations observed in NRTI and NNRTI resistance among the predominant CRF01_AE strains. The most common NRTI mutations observed were M184V, K65R, and S68G, whereas the most common NNRTI mutations were K103N, Y181C, and G190A. The study also found a high prevalence of M184V minority variants (0.5-20%) in treatment-naive patients, which could increase the risk of virological failure in 3TC-containing regimens. The findings of this study highlight the importance of comprehensive drug resistance surveillance and access to resistance testing to guide optimal first-line antiretroviral treatment selection and to manage the growing HIV-1 epidemic in the Philippines. The development of effective strategies to prevent and manage drug resistance is crucial to ensuring the long-term success of HIV treatment programs in the country.